1994
DOI: 10.1159/000282608
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Prostaglandins E<sub>1</sub> E<sub>2</sub> and F<sub>2α</sub> on Contractility and cAMP and cGMP Contents in Lower Urinary Tract Smooth Muscle

Abstract: Prostaglandin (PG) E1 E2 and F contracted smooth muscle strips from male adult rabbit urinary bladder. Contractile responses to each PG were significantly greater in urinary bladder body than in urinary bladder base. The magnitude of contractile response to each PG was F > E2 > E1 in both of the bladder body and the bladder base. These contractions were almost completely eliminated by a calcium entry blocker, verapamil but not by atropine, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 8 publications
1
15
0
1
Order By: Relevance
“…PGE 1 , PGE 2 , and PGF 2␣ all contract detrusor muscle, but in the urethra, PGE 1 and PGE 2 cause relaxation, whereas PGF 2␣ produces contraction (Andersson, 1993). This pattern of effects has been demonstrated in animal (Persson and Andersson, 1976;Khanna et al, 1978;Gotoh et al, 1986;Morita et al, 1994;Pinna et al, 1996), as well as human urethral smooth muscle (Andersson et al, 1978a). In women receiving PGE 2 intravesically or intraurethrally, a decrease in the maximum urethral pressure and a reduction of the closure pressure were found (Andersson et al, 1978a;Schussler, 1990).…”
Section: Pharmacology Of the Lower Urinary Tractmentioning
confidence: 56%
See 1 more Smart Citation
“…PGE 1 , PGE 2 , and PGF 2␣ all contract detrusor muscle, but in the urethra, PGE 1 and PGE 2 cause relaxation, whereas PGF 2␣ produces contraction (Andersson, 1993). This pattern of effects has been demonstrated in animal (Persson and Andersson, 1976;Khanna et al, 1978;Gotoh et al, 1986;Morita et al, 1994;Pinna et al, 1996), as well as human urethral smooth muscle (Andersson et al, 1978a). In women receiving PGE 2 intravesically or intraurethrally, a decrease in the maximum urethral pressure and a reduction of the closure pressure were found (Andersson et al, 1978a;Schussler, 1990).…”
Section: Pharmacology Of the Lower Urinary Tractmentioning
confidence: 56%
“…In women receiving PGE 2 intravesically or intraurethrally, a decrease in the maximum urethral pressure and a reduction of the closure pressure were found (Andersson et al, 1978a;Schussler, 1990). Morita et al (1994) showed that PGE 1 and PGE 2 significantly relaxed the male rabbit urethral smooth muscle strips, whereas PGF 2␣ caused contraction. In the strips, cAMP, but not cGMP, increased significantly after administration of PGE 1 or PGE 2 .…”
Section: Pharmacology Of the Lower Urinary Tractmentioning
confidence: 96%
“…1 However, few investigations have addressed the cAMP-and cGMP-mediated signal transduction pathways and their key enzymes in the mammalian urethra. Morita et al 9,42 examined the effects of PGE 1, PGE 2, isoproterenol, and SNP on the contractile force and tissue content of cAMP and cGMP in the rabbit bladder and urethra. They concluded that these substances, mediated by both cGMP and cAMP, but mainly by cGMP, can induce relaxation of the urethra.…”
Section: Pdes In the Urethramentioning
confidence: 99%
“…But how far are local urinary levels of the inflammatory mediators relevant to the inflammatory process at all? In particular, anticholinergics and BoNT-A are acting by different receptor mediated signal transduction pathways affecting Ca ++ influx with impact on PGE2 release [29, 30]. The regulation and action of prostaglandins in the urinary bladder are still obscure.…”
Section: Discussionmentioning
confidence: 99%